2021
DOI: 10.1097/iop.0000000000001902
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction and Management of Postoperative Complications Following Ablative Carbon Dioxide Laser Resurfacing of the Lower Eyelids

Abstract: Purpose: To describe postoperative management following ablative carbon dioxide laser resurfacing of the lower eyelids. Methods: A retrospective review of patients who consecutively underwent bilateral lower eyelid ablative carbon dioxide laser resurfacing by a single experienced oculoplastic surgeon over a 6-year period was conducted. Patient satisfaction, aesthetic outcomes, and postoperative complications were evaluated as adjunctive or monotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…There was a 72.5% reduction in the appearance of the wrinkles. However, the study by Kim et al, 9 Reported that patient satisfaction was overall high, with 363 (85.6%) very satisfied and 48 (11.3%) satisfied with the aesthetic outcome of lower eyelid laser resurfacing. They concluded that Ablative carbon dioxide laser resurfacing of the lower eyelids can be a useful tool in the armamentarium of the experienced oculoplastic surgeon, with excellent aesthetic results, high patient satisfaction, and low complication rates as adjunctive or monotherapy.…”
Section: A B 1486mentioning
confidence: 98%
See 1 more Smart Citation
“…There was a 72.5% reduction in the appearance of the wrinkles. However, the study by Kim et al, 9 Reported that patient satisfaction was overall high, with 363 (85.6%) very satisfied and 48 (11.3%) satisfied with the aesthetic outcome of lower eyelid laser resurfacing. They concluded that Ablative carbon dioxide laser resurfacing of the lower eyelids can be a useful tool in the armamentarium of the experienced oculoplastic surgeon, with excellent aesthetic results, high patient satisfaction, and low complication rates as adjunctive or monotherapy.…”
Section: A B 1486mentioning
confidence: 98%
“…Also, Griffin et al, 8 reported that all cases had lower lid dermatochalasis the studied groups were comparable as regard preoperative complain. Kim et al, 9 stated that all cases had bilateral lower eyelid puffiness. In the current study regarding complications, we found that in group (A) there was 2(20.0%) had incomplete correction while in group (B) 4(40%) had Increased periocular wrinkles.…”
Section: A B 1486mentioning
confidence: 98%
“…On the other hand, fractionated CO2 laser resurfacing was comparable to traditional ablative resurfacing, but had lower risk of complications and shorter recovery time. 82,83 A study by Kim et al 84 with fractional ablative CO2 laser resurfacing revealed low risk of infections, mainly viral. The most common complication was inflammatory hyperpigmentation, which occurred in about 10% of patients but could be easily treated locally.…”
Section: Laser Treatment and Microsurgical Techniquesmentioning
confidence: 99%
“…The first laser‐assisted blepharoplasty procedure was developed by Baket in 1980, but despite initial excitement and a relevant side effect—excessive thermal damage that results in scars—the practice was never widely adopted 15–16 . It was only possible to resolve this issue in the early 1990s with the development of new high energy pulsed carbon dioxide (CO 2 ) lasers; these innovations enabled medical professionals to coagulate and cut tissues with minimal thermal injury while achieving consistent results 17,18 …”
Section: Introductionmentioning
confidence: 99%
“…[15][16] It was only possible to resolve this issue in the early 1990s with the development of new high energy pulsed carbon dioxide (CO 2 ) lasers; these innovations enabled medical professionals to coagulate and cut tissues with minimal thermal injury while achieving consistent results. 17,18 The aim of this study was to evaluate the efficacy and safety of a new CO 2 laser-assisted blepharoplasty technique applied to the upper and lower eyelids.…”
mentioning
confidence: 99%